Komparasi Kinerja Konfigurasi Kombinasi dan Single Rod Guide Berdasarkan Data Historis Gross Production pada Sumur J di Sumur Ral Lapangan Aura - Rama Arya Lingara; Abdul Gafar Karim; Eka Megawati; Aici Ichtiarizak Machrifah; Nijusiho Manik (INDO PUBLISHING, 2026)
J-type deviation wells that use a Sucker Rod Pump (SRP) system with a Hydraulic Pumping Unit (HPU) are prone to friction between the sucker rod and the tubing,which can affect production performance. This study aims to compare the gross production characteristics of the combined configurations of a single double rod guide and a single rod guide, using historical production data from the J well in the Aura Field. The analysis was conducted quantitatively based on data on production, well trajectory and workover, using the parameters of average gross production and production slope. The results of the study show that the combined configuration yielded an average gross production of 312.11 BFPD and a slope of −1.016 BFPD/day, whilst the singlerod guide configuration yielded 210.93 BFPD and a slope of −1.730 BFPD/day. These results indicate that the combined configuration is capable of maintaining a higher production rate with a slower decline rate, making it more effective in maintaining production stability in wells with similar characteristics.